Imipenem susceptibility in Gram-negative and positive microorganisms - Ozerol, I.Halil; Sonmez, Emine; Ozbilge, Hatice; Nese Tastekin, Bio. (Annals of Medical Research, 2021)
None
Keywords: s : Imipenem-cilastatin, polimicrobic infeetion, E.coli, Pseudomonas, Proteus, Klebsiella, Enterobacter, S. aureus.